Integrating YouTube Video Analysis into Pre-Writing Activities to Foster Idea Generation and Coherence in Writing - Farid Rizaldi; Fadhila Fauziah Putri; Rita Hartati (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
This study explored how integrating YouTube video analysis into pre-writing activities can support idea generation and coherence in students’ writing. Writing is often challenging for EFL learners, especially in developing ideas and organizing them logically. To address this, the study used YouTube as a pre-writing tool that provides visual and auditory input to stimulate creativity and critical thinking. This research employed a descriptive qualitative method using a YouTube video titled “Writing Process: Pre-Writing” from Mr. Paige’s English Writing Center and open-ended questionnaires answered by 30 English Literature students. The findings showed that 70% of students agreed that watching or analyzing YouTube videos before writing helped them generate ideas more easily, while 56.7% found the activities more engaging and 53.3% reported better organization of thoughts. Additionally, 50% of participants felt more confident to start writing, and 63.3% believed that teachers should integrate video analysis into writing classes. These results indicate that YouTube-based pre-writing activities enhance idea generation, coherence, and motivation in writing. Overall, YouTube video analysis proves to be an effective digital learning strategy that combines creativity, engagement, and logical organization in the writing process.